The Development of e-UKBM of Acid-Bases in Chemistry Based on Problem Based Learning Integrated with Sikkanese Lokal Culture: The Development of e-UKBM of Acid-Base in Chemistry Based on Problem-Based Learning Integrated with Sikkanese Local Culture - M.A Yohanita Nirmalasari; Klaudius Ware; Maria Setiawati Menge Badhi (Pusat Data dan Teknologi Informasi Kementerian Pendidikan Kebudayaan, Riset dan Teknologi, 2022)
Penelitian ini dilatarbelakangi oleh permasalahan penggunaan sumber belajar yang kurang efektif pada masa pandemi dan kebosanan peserta didik dalam mengikuti proses pembelajaran Kimia terutama materi asam basa. Untuk mengatasinya, dilakukan penelitian pengembangan unit kegiatan belajar mandiri dalam bentuk elektronik (e-UKBM) untuk memfasilitasi pembelajaran selama work from home. Tujuan penelitian ini adalah untuk: 1) mengetahui cara mengembangkan e-UKBM Kimia Asam Basa untuk peserta didik dan pendidik; dan 2) menguji kelayakan e-UKBM Kimia Asam Basa berdasarkan hasil pengembangan pada tahap 1. Kemasan pembelajaran e-UKBM mengadopsi model problem-based learning yang diintegrasikan dengan kearifan lokal daerah Sikka. Metode yang digunakan adalah research and development dengan model pengembangan 4D (Define, Design, Develop, Disseminate). Subjek penelitian ini adalah peserta didik kelas XI SMAN 1 Maumere, SMAN 2 Maumere, dan SMAK St. Gabriel Maumere yang berjumlah 40 orang serta pendidik berjumlah 4 orang. Berdasarkan hasil perhitungan persentase kevalidan diperoleh nilai 81,37% (valid). Selanjutnya, e-UKBM Kimia dinyatakan layak digunakan dalam proses pembelajaran Kimia berdasarkan hasil uji coba lapangan awal dan uji coba lapangan luas. Hasil uji coba lapangan awal oleh peserta didik adalah 102,37 (kategori baik) dan pendidik adalah 105,00 (kategori baik). Pada uji lapangan luas oleh peserta didik hasilnya adalah 129,05 (kategori sangat baik) dan oleh pendidik adalah 144,00 (kategori sangat baik) This research is triggered by the ineffectiveness problem of learning resource utilization during the pandemic era and the students’ boredom in attending the chemistry lesson, especially for acid-base material. To overcome it, the researchers try to carry out a research on the development of electronic Independent Learning Activity Unit (e-UKBM) to facilitate learning activity during the ‘work from home’ period. The purposes of this research are to: 1) know how to develop acid-base chemistry e-UKBM for students and teachers; and 2) test the acid-base chemistry e-UKBM feasibility based on the development in phase 1. The packaging of the e-UKBM adopts problem-based learning method which is integrated with Sikkanese local culture. The applied research method is research and development (R&D) with 4D development model (Define, Design, Develop, Disseminate). The respondents of this research are the grade XI students of SMAN 1 Maumere, SMAN 2 Maumere, and SMK St. Gabriel Maumere amounting 40 students and 4 teachers. Based on the validity percentage calculation, the result shows the value of 91,37% (valid). Then, the chemistry e-UKBM is stated to be feasible to be used in chemistry learning process based on the initial as well as broad field tests. The result of initial field test by the students indicates the value of 102,37 (good category), and by the teachers indicates the value of 105,00 (good category). The result of broad field test by the students indicates the value of 129,05 (very good category), and by the teachers indicates the value of 144,00 (very good category)